Analisa Beban Kerja Mental Operator Dengan Metode NASA TLX Di PT XYZ - Sulistiyo, Wawan; Vitasari, Prima (Jurnal Rekayasa Sistem Industri, 2024)
PT XYZ is a fermentation industry that uses Human Machine Interfaces (HMI) in the production process. With high mental workload of operators, it can disrupt company productivity. In 2021, the achievement of the percentage of production failure targets at PT XYZ has not reached the set target. The purpose of this study is to measure and make improvements to the mental workload at PT XYZ. The research method is to measure mental workload using the NASA TLX questionnaire, conduct data analysis using descriptive statistics, and conduct a paired t-test to compare the results of mental workload before and after improvement.. From the research results, the mental workload score was 72.64 in the high category. Of the six NASA TLX dimensions, operators experienced time demands of 24.1%, effort 23.1%, mental demands 22.3%, performance 20.2%, physical demands 9.3% and frustration 1.0%. The improvement results can reduce the high mental workload of operator from 82 to 74 with a significant level of 0.004, and increase the low mental workload of operators from 53 to 66 with a significant level of 0.129.